MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA KELAS VIII SMP NEGERI 2 CARIU PADA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL DENGAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION (RME) - Syamsudin, Nurlia; Afrilianto, M; Rohaeti, Euis Eti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The purpose of this researchis to improve mathematical communication ability of the students in class VIII A in two variabels equation system by using Realistic Mathematic Education (RME) approach at SMPN 2 Cariu. The type of this research is Classroom Action Research (CAR) by using spiral research model from Kemmis and McTaggart with the sample of this research is all students of class VIII A SMPN 2 Cariu. This research consists of two cycles where each cycle consists of planning, implementation, observation and replection, which is before and after this research is given the instruments in the essay from in each cycle, there is an observation sheet of the teacher and students activity during in the learning progress. The result of this research is to indicate the students mathematical communication aibility can be improve through the application of the Realistic Mathematic Education (RME) approach.